1985
DOI: 10.2466/pms.1985.61.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Congenital Spasticity on Fundamental Frequency

Abstract: 5 normal speakers and 5 speakers with congenital upper motor-neuron damage repeatedly spoke a three-work sentence stressing the first, second, or third words. Fundamental frequency was measured for each word and over each sentence. Analysis showed that the spastics' mean fundamental frequency was significantly higher than the normals', regardless of utterance. Also, spastics were more restricted in their prosodic maneuvering above this average fundamental frequency. Despite this finding, the spastics were capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The production data support this claim. Similarly, given that narrowed fundamental frequency range has often been noted as a hallmark of dysarthria (Hardy, 1983;Jacques, Rastatter, & Sullivan, 1985;Schlenck, Bettrich, & Willmes, 1993;Wit, Maassen, Gabreels, & Thoonen, 1993), children may have had difficulty producing 3 distinct pitch categories. The results indicated that listeners often confused medium-pitch vocalizations for high-and low-pitch sounds.…”
Section: Discussionmentioning
confidence: 99%
“…The production data support this claim. Similarly, given that narrowed fundamental frequency range has often been noted as a hallmark of dysarthria (Hardy, 1983;Jacques, Rastatter, & Sullivan, 1985;Schlenck, Bettrich, & Willmes, 1993;Wit, Maassen, Gabreels, & Thoonen, 1993), children may have had difficulty producing 3 distinct pitch categories. The results indicated that listeners often confused medium-pitch vocalizations for high-and low-pitch sounds.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced pitch variation within sentences due to rigidity, while speakers with cerebral palsy tend to display extreme variability related to reduced control of the laryngeal mechanism (Darley, Aronson & Brown, 1969b;Jacques, Rastatter & Sullivan, 1985). As a result of these different characteristics, both groups are susceptible to errors in tone production.…”
Section: Phonology Mandarin Has 22 Initial Consonantsmentioning
confidence: 99%
“…Darley et al (1969b) reported that phonatory stenosis and incompetence, which were due to abnormalities in the laryngeal mechanism, affected different types of dysarthria. Jacques et al (1985) observed a reduction in laryngeal control in cerebral palsy patients with congenital spasticity. Theodoros and Murdoch (1994) reported a high incidence, and a wide range, of laryngeal dysfunction in dysarthria associated with closed-head injury.…”
Section: Introductionmentioning
confidence: 95%